2016
DOI: 10.1038/srep36361
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of longevity and senescence reveal variable survival benefits of living in zoos across mammals

Abstract: While it is commonly believed that animals live longer in zoos than in the wild, this assumption has rarely been tested. We compared four survival metrics (longevity, baseline mortality, onset of senescence and rate of senescence) between both sexes of free-ranging and zoo populations of more than 50 mammal species. We found that mammals from zoo populations generally lived longer than their wild counterparts (84% of species). The effect was most notable in species with a faster pace of life (i.e. a short life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
154
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(174 citation statements)
references
References 35 publications
6
154
2
1
Order By: Relevance
“…The primary aim of our study is to apply a systematic meta‐analytical approach to evaluate the evidence for the occurrence of immunosenescence in wild vertebrates (amniotes). We include free‐living and captive populations for comparison to gain insight into what extent environmental variation can explain variation in immunosenescence (for example, actuarial senescence patterns differ between wild and captive (zoo) populations; Tidière et al ). Senescence is the result of an increase in susceptibility to environmental and physiological challenges with age (Medawar ), including infections and disease, which can be difficult to simulate in captivity (Pedersen & Babayan ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of our study is to apply a systematic meta‐analytical approach to evaluate the evidence for the occurrence of immunosenescence in wild vertebrates (amniotes). We include free‐living and captive populations for comparison to gain insight into what extent environmental variation can explain variation in immunosenescence (for example, actuarial senescence patterns differ between wild and captive (zoo) populations; Tidière et al ). Senescence is the result of an increase in susceptibility to environmental and physiological challenges with age (Medawar ), including infections and disease, which can be difficult to simulate in captivity (Pedersen & Babayan ).…”
Section: Introductionmentioning
confidence: 99%
“…First, actuarial senescence is a nearly ubiquitous process in the living world (Nussey, Froy, Lemaitre, Gaillard, & Austad, ; Shefferson, Jones, & Salguero‐Gómez, ). Second, patterns of senescence can be highly variable among species (Colchero et al, ; Jones et al, ; Tidière et al, ). Comparative analyses have shown that senescence patterns across multicellular organisms can be predicted by ecological traits, lifestyles and covariation among life‐history traits (Gaillard et al, ; Péron, Gimenez, Charmantier, Gaillard, & Crochet, ; Ricklefs, ; Salguero‐Gómez & Jones, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis of laboratory studies found no effect of early diet on life span (English & Uller, ), but the simplified environments of laboratory or captive studies may produce results different from those observed in the wild (Briga & Verhulst, ; Kawasaki, Brassil, Brooks, & Bonduriansky, ; Tidière et al., ). In addition, not all species are suitable for laboratory study.…”
Section: Introductionmentioning
confidence: 99%